Ultrasound elastography to determine the layered mechanical properties of articular cartilage and the importance of such structural characteristics under load - McCredie, A; Stride, E; Saffari, N (2009)
Articular cartilage is an important load bearing surface in joints. Prone to damage and with limited self-repair ability, it is of interest to tissue engineers. Tissue implant design requires full mechanical characterisation of healthy native tissue. A layered organisation of reinforcing collagen fibrils exists in healthy articular cartilage and is believed to be important for correct tissue function. However, the effect of this on the local depth-dependent elasticity is poorly characterised. In this study, quasi-static ultrasound elastography is used both to compare the depthdependent elastic properties of cartilage structures with two different fibril arrangements and to monitor changes in the elastic properties of engineered samples during development. Results show global and local elastic properties of the native tissues and highlight the differences caused by fibril architecture. At increasing culture periods, results from the engineered tissue demonstrate an increase in elastic stiffness and the time taken to reach equilibrium under a quasi-static displacement. The study suggests suitability of ultrasound elastography for design and monitoring engineered articular cartilage. ©2009 Crown.